Overexpression of soybean GmPLDγ enhances seed oil content and modulates fatty acid composition in transgenic Arabidopsis - Bai, Yang (Plant science : an international journal of experimental plant biology, 2020)
Copyright © 2019 Elsevier B.V. All rights reserved.